PinX1 is recruited to the mitotic chromosome periphery by Nucleolin and facilitates chromosome congression - Li, Na (Biochem Biophys Res Commun, 2009)
Mitotic chromosome movements are orchestrated by interactions between spindle microtubules and chromosomes. It is well known that kinetochore is the major site where microtubule-chromosome attachment occurs. However, the functions of other domains of chromosome such as chromosome periphery have remained elusive. Our previous studies show that PinX1 distributes to chromosome periphery and kinetochore during mitosis, and harbors the microtubule binding activity. Here we report that PinX1 interacts with Nucleolin, a chromosome periphery protein, through its C-termini. Deconvolution microscopic analyses show PinX1 mainly co-localizes with Nucleolin at chromosome periphery in prometaphase. Moreover, depletion of Nucleolin abolishes chromosome periphery localizations of PinX1, suggesting a functional interrelationship between PinX1 and Nucleolin. Importantly, repression of PinX1 and Nucleolin abrogates chromosome segregation in real-time mitosis, validating the functional importance of PinX1–Nucleolin interaction. We propose PinX1 is recruited to chromosome periphery by Nucleolin and a complex of PinX1 and Nucleolin is essential for faithful chromosome congression.